Abnormal structure-function relationships in hereditary dystonia - Carbon, M.; Eidelberg, D. (Neuroscience, 2009)
Primary torsion dystonia (PTD) is a chronic movement disorder manifested clinically by focal or generalized sustained muscle contractions, postures, and/or involuntary movements. The most common inherited form of PTD is associated with the DYT1 mutation on chromosome 9q34. A less frequent form is linked to the DYT6 locus on chromosome 8q21-22. Both forms are autosomal dominant with incomplete (∼30%) clinical penetrance. Extensive functional and microstructural imaging with positron emission tomography (PET) and diffusion tensor MRI (DTI) has been performed on manifesting and non-manifesting carriers of these mutations. The results are consistent with the view of PTD as a neurodevelopmental circuit disorder involving cortico-striatal-pallido-thalamocortical (CSPTC) and related cerebellar–thalamo-cortical pathways. Studies of resting regional metabolism have revealed consistent abnormalities in PTD involving multiple interconnected elements of these circuits. In gene carriers, changes in specific subsets of these regions have been found to relate to genotype, phenotype, or both. For instance, genotypic abnormalities in striatal metabolic activity parallel previously reported reductions in local D2 receptor availability. Likewise, we have identified a unique penetrance-related metabolic network characterized by increases in the pre–supplementary motor area (SMA) and parietal association areas, associated with relative reductions in the cerebellum, brainstem, and ventral thalamus. Interestingly, metabolic activity in the hypermetabolic areas has recently been found to be modified by the penetrance regulating D216H polymorphism. The DTI data raise the possibility that metabolic abnormalities in mutation carriers reflect adaptive responses to developmental abnormalities in the intrinsic connectivity of the motor pathways. Moreover, findings of increased motor activation responses in these subjects are compatible with the reductions in cortical inhibition that have been observed in this disorder. Future research will focus on clarifying the relationship of these changes to clinical penetrance in dystonia mutation carriers, and the reversibility of disease-related functional abnormalities by treatment.